Nine Common Errors in Building a New World-Class University - Salmi, Jamil (International Higher Education, 2011)
Launching a new tertiary education institution that aspires to attain the highest possible standards is a noble but extremely difficult enterprise. There are many commonly observable errors. The decision to build a world-class university must always be examined within the proper context to ensure full alignment with the national tertiary education strategy and to avoid distortions in resource-allocation patterns within the sector.